Spanish nationality of the inhabitants of Western Sahara. Commentary to the Judgment of the Provincial Hearing of Barcelona, from November 11, 2019. - Ortega Giménez, Alfonso (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
Since the Judgment of the Supreme Court of October 28, 1998, it has been understood that the way through which the natives of the Sahara, who were born when this territory was a Spanish province, can access Spanish nationality, is the recognition of state possession, indicated by article 18 of our Civil Code. In this sense, the Judgment of the Provincial Court of Barcelona, of November 11, 2019, considers an appeal admitting the registration of nationality for possession of the nationality taking into account the testimonial and documentary evidence provided by the appellant, all of which is proof of that the plaintiff was in possession of both the general and the specific documentation referred to in the regulations, in addition to other documents that accredited the exercise of activities proper to the Spanish national, for which it is proven “the possession of the state of Spanish national by the actor, as well as its continued use, for at least ten years ”, affirming, consequently,“ the consolidation of the de facto possession of its Spanish nationality ”for the aforementioned term and“ in accordance with good faith ”, such and as established in article 18 of the Civil Code.
Keywords: Spanish nationality; recognition for possession of state; recovery of nationality; Sahara